Evolucao materno-infantil da contaminacao por mercurio: Estudo em duas populacoes indigenas brasileiras - Gonçalves, Aguinaldo; Ferrari, Íris; Barbosa, Antônio; Serra, Olympio; Padovani, Carlos Roberto [UNESP]; Brasileiro, Iara; Da Silva E Gonçalves, Neusa Nunes (My University, 1998)
Considering the severity of Hg intoxication to human health and the frequent use of the metal in gold prespection on Brazilian Amazonia, an extensive project in being developed in order to quantify such conditions in two indigenous Kayapo populations, inhabitants of South of Para State, Gorotire and Djudjetikitire. This paper reports evolution of this contamination on mothers and babies. During puerperium, it was registered both an important decline on dosimetric values observed before in pregnancy and the occurrence of expressive levels in the babies. Such data are discussed based on contemporary medical-biologic conceptions, since it raises conceptual review of the matter.
Evolution of mercury contamination on mothers and babies: Study in two Brazilian indigenous populations
Keywords: Brazilian Amazonia; Indians; Mercury intoxication; Mothers and babies; brazil; human; incidence; major clinical study; mercurialism; placental transfer; puerperium